Pulmonary Hypertension Due to Left Heart Disease - Gerges, Mario; Gerges, Christian; Naeije, Robert; Lang, Irene M. (Seminars in Respiratory and Critical Care Medicine, 2017)
Pulmonary hypertension (PH) due to left heart disease (PH-LHD) is a significant predictor of outcome for patients with any type of heart failure (HF), and represents a subset of PH affecting a large number of patients. Because the condition is no standalone inherent pulmonary vascular disorder but the consequence of heart disease, its understanding is dependent on a thorough insight in current HF epidemiology, pathophysiology, diagnosis, and treatments. Although the age-specific incidence of HF is decreasing, this trend is less dramatic for HF with preserved ejection fraction than for HF with reduced ejection fraction. Both the current 2015 ESC/ERS guidelines for the diagnosis and treatment of PH, and the 2016 ESC guidelines for the diagnosis and treatment of acute and chronic HF have adopted new insights in the current understanding of PH-LHD (PH group 2), but no consensus has been reached. Due to multimorbidity, advanced age, referral biases, and a large proportion of noncardiovascular deaths in this population, proper hemodynamic and clinical characterization of patients with and without significant pulmonary vascular disease is important. Definitions largely depend on fluid status which should be assessed prior to any hemodynamic assessment. Benefit from pulmonary arterial hypertension–targeted treatments appears unlikely from today's perspective, but there is an immense unmet need for any treatments of this condition, and proper trials still have to be done.
Keywords: heart failure; hemodynamics; left heart disease; pulmonary hypertension